THE FAMILY HEALTH TEAM AND THE USE OF DRUGS AMONG ADOLESCENTS* - Simone Campos Ferreira; Richardson Miranda Machado (Universidade Federal do Paraná, 2013)
This cross-sectional study, with an epidemiological and descriptive character, aimed to analyze the use of alcohol and/or drugs by adolescents in the territory of a Family Health Strategy team in 2011. 142 adolescents were interviewed, responding to two questionnaires, one with socio-economic data, and the other titled Drug Use Screening Inventory. Similarity was found between the sexes; higher consumption of drugs between the ages of 10 and 12 and 16 and 18; and lower consumption among Roman Catholics and Pentecostalists. The most-consumed substances were analgesics, alcohol and tobacco; greater intensity of problems was observed in the areas of leisure and recreation, social competence, and patterns of behavior. The data presents information relevant to the planning of strategies for preventing drug use in adolescence.